2002
DOI: 10.1152/ajpcell.00009.2001
|View full text |Cite
|
Sign up to set email alerts
|

Isolated mouse pancreatic β-cells show cell-specific temporal response pattern

Abstract: The length of the silent lag time before elevation of the cytosolic free Ca2+ concentration ([Ca2+]i) differs between individual pancreatic beta-cells. One important question is whether these differences reflect a random phenomenon or whether the length of lag time is inherent in the individual beta-cell. We compared the lag times, initial dips, and initial peak heights for [Ca2+]i from two consecutive glucose stimulations (with either 10 or 20 mM glucose) in individual ob/ob mouse beta-cells with the fura 2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Rest periods are important for producing repetitive stimulation of in vitro [Ca 2+ ] i responses (Donahue et al 2003;Larsson-Nyren et al 2002;Pakhtusova et al 2003;Prentki et al 1988). MC3T3 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rest periods are important for producing repetitive stimulation of in vitro [Ca 2+ ] i responses (Donahue et al 2003;Larsson-Nyren et al 2002;Pakhtusova et al 2003;Prentki et al 1988). MC3T3 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These parameters have been implicated in the regulation of downstream biological events such as gene expression, differentiation, and apoptosis in many cell types (Berridge et al 1998). It has been hypothesized that [Ca 2+ ] i wave patterns in individual cells are unique for different agonists (Huang et al 2000;Larsson-Nyren et al 2002;Prentki et al 1988;Toescu 1995). The pattern is called a "calcium finger-print" (Prentki et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Isolated b-cells and small cell clusters show a high degree of functional heterogeneity (Pralong et al 1990, Herchuelz et al 1991, Pipeleers et al 1994. We recently reported that nutrient-induced Ca 2C and NADH response patterns are also cell-specific, i.e., reproducible with regard to timing and magnitude of response (Larsson-Nyrén et al 2002, Pakhtusova et al 2003, Gustavsson et al 2005. However, the cell specificity of mitochondrial metabolism seems to be blunted in diabetes and obesity (Gustavsson et al 2005).…”
Section: Introductionmentioning
confidence: 99%